2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26120
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Growth of Empathy Among Engineering Students

Abstract: interests include developing pedagogical strategies to improve STEM students' ethical reasoning skills; exploring the role of empathy within design, innovation and sustainability; synthesizing the influence of societal and individual worldviews on decision-making; assessing STEM students' learning in the spaces of design, ethics, and sustainability; and exploring the impact of pre-engineering curriculum on students' abilities and career trajectories. The Development and Growth of Empathy among Engineering Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 49 publications
(70 reference statements)
1
51
0
2
Order By: Relevance
“…While the development of empathic perspective‐taking is essential to the professional and ethical practice of engineers, we lack knowledge about the processes that promote the empathic formation of engineering students (Hess & Fila, ). In a developmental sense beyond engineering, there are numerous stage or schematic models that depict development from less to more advanced cognitive, social, or moral stages through a series of transitional points.…”
Section: Background and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…While the development of empathic perspective‐taking is essential to the professional and ethical practice of engineers, we lack knowledge about the processes that promote the empathic formation of engineering students (Hess & Fila, ). In a developmental sense beyond engineering, there are numerous stage or schematic models that depict development from less to more advanced cognitive, social, or moral stages through a series of transitional points.…”
Section: Background and Theorymentioning
confidence: 99%
“…While there has been limited research on empathic development, in 2011, Strobel et al found 22 papers that explicitly focused on empathy in engineering in general. More recently, there has been a much more concerted focus on empathy as a potential concept, disposition, or skill that should be integrated into engineering (Fila, Hess, Purzer, & Dringenberg, 2016;Gray, Yilmaz, Daly, Seifert, & Gonzalez, 2015;Hess, Strobel, Pan, & Wachter Morris, 2017;Hess, Strobel, & Pan, 2016;Rasoal, Danielsson, & Jungert, 2012;Walther et al, 2017). Researchers have begun exploring empathy's functional role (e.g., the affective and cognitive processes of or relations between stakeholders) within multiple engineering educational contexts, including design Gray et al, 2015), service-learning (Lynch et al, 2014;Zoltowski, Oakes, & Cardella, 2012), communication (Leydens & Lucena, 2009;Walther, Miller, & Kellam, 2012), and ethics (Hess, Beever, et al, 2017;Vallero, 2008;Walther et al, 2017).…”
Section: Conceptual Framingmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas oito distinções sobre empatia propostas por Batson podem ser sintetizadas da seguinte maneira (HESS & FILA, 2016): (i) precisão empática ou teoria da mente; (ii) mimetismo motor; (iii) contágio emocional; (iv) projeção: imaginar-se na posição de outro; (v) tomada de perspectiva: imaginar o outro; (vi) tomada de perspectiva: imaginar-se como se fosse o outro; (vii) aflição empática; e (viii) preocupação empática ou simpatia.…”
Section: Considerações Sobre Empatiaunclassified
“…A more holistic understanding of the patient may provide for a more effective design process. In the engineering education field in general, a number of investigations have been conducted to explore the relationship and importance of empathy, self-awareness, and social-awareness in engineering students [11][12][13][14]. These studies reveal the importance of empathy for effective innovation and engineering design.…”
Section: Introductionmentioning
confidence: 99%